2009
DOI: 10.1055/s-0029-1233474
|View full text |Cite
|
Sign up to set email alerts
|

Entwicklung und Erprobung von Qualitätsindikatoren für die ambulante Pflege in der Schweiz

Abstract: The Swiss version of RAI-HC provides a viable instrument for measuring quality of home care. The application of consistent assessment rules should be improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…After removal of duplicates and title/abstract screening, 21 studies were potentially relevant. Four studies met the selection criteria after full-text screening [29,30,37,38]. Reference tracking of the eligible studies identified no additional article.…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After removal of duplicates and title/abstract screening, 21 studies were potentially relevant. Four studies met the selection criteria after full-text screening [29,30,37,38]. Reference tracking of the eligible studies identified no additional article.…”
Section: Search Resultsmentioning
confidence: 99%
“…Description of studies Table 1 shows the main characteristics of the selected papers. Three studies specified the development and validation process of separate RAI-HC QI sets, namely, interRAI's 1st generation QI set developed by Hirdes et al [37], the Swiss RAI-HC QI set developed by Burla et al [29], and interRAI's 2nd generation QI set developed by Morris et al [30]. One study by Dalby et al [38] explored the effects of risk adjustment for interRAI's 1st generation QI set.…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…144,145 Specific tools evaluated included the Resident Assessment Instrument -Homecare. [146][147][148][149][150] Other tools evaluated were the Support Needs Assessment, the Five-Repetition Sit-to-Stand Test, the Care Dependency Scale, and the Palliative Prognostic Index. 146,[151][152][153] What is the scope of technology and the future direction of homecare delivery?…”
Section: Treatment-related (Five Studies)mentioning
confidence: 99%